2018
DOI: 10.1111/cas.13750
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐finding study of the checkpoint kinase 1 inhibitor, prexasertib, in Japanese patients with advanced solid tumors

Abstract: Prexasertib is a novel inhibitor of checkpoint kinase 1. The primary objective of this study was to evaluate prexasertib tolerability in Japanese patients with advanced solid tumors. This nonrandomized single‐arm open‐label phase 1 study of prexasertib consisted of 2 dose levels, 80 mg/m2 and the global‐recommended dose based on a US study of 105 mg/m2, administered intravenously once every 14 days (n = 6 for each dose). Transition to the higher dose proceeded if the frequency of dose‐limiting toxicity observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…The single-agent RP2D of prexasertib administered in adult patients on an every 14-day schedule was determined to be 105 mg/m 2 . 11,19,20 In a phase 1b expansion that treated over 100 patients with squamous cell carcinoma at this dose and schedule, 89% of patients had treatment-emergent grade 3/4 neutropenia, which is similar to the 100% seen on our study. 19 Rates of grade 3/4 anemia (14%) and approximately 24 hours and the drug exposure measured as the AUC 0-24hr was greater than the median AUC 0-72hr value (1896 ng•hr/mL) predicted for efficacy based on the Calu-6 preclinical PK/PD model.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The single-agent RP2D of prexasertib administered in adult patients on an every 14-day schedule was determined to be 105 mg/m 2 . 11,19,20 In a phase 1b expansion that treated over 100 patients with squamous cell carcinoma at this dose and schedule, 89% of patients had treatment-emergent grade 3/4 neutropenia, which is similar to the 100% seen on our study. 19 Rates of grade 3/4 anemia (14%) and approximately 24 hours and the drug exposure measured as the AUC 0-24hr was greater than the median AUC 0-72hr value (1896 ng•hr/mL) predicted for efficacy based on the Calu-6 preclinical PK/PD model.…”
Section: Discussionsupporting
confidence: 77%
“…11 There are limited published adult PK data for prexasertib administered as a single agent in phase I clinical trials, and no adult data at the pediatric RP2D. 11,20 Although an MTD was not reached in our study, the dose of 150 mg/m 2 was well tolerated and provided twice the exposure than the RP2D from either adult study. In the absence of strong PK or PD data to suggest otherwise, the typical approach taken in pediatric phase 1 trials is to use the estimated highest tolerable dose as the RP2D.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In patients who administered BI 2536 or volasertib, neutropenia was the most frequently observed adverse event, and about 30%-40% of the patients experienced grade 3 or 4 neutropenia (23)(24)(25)27,28). Similarly, hematological adverse events were frequently observed in the patients that were treated with prexasertib, and almost all the patients experienced grade 3 or 4 neutropenia (44)(45)(46)(47). Therefore, the hematological toxicity of these drugs should be kept in mind; however, it is important to also note that all clinical trials have concluded the safety profile.…”
Section: Discussionmentioning
confidence: 99%
“… 48 Although dose-limiting cardiac toxicities were reported in 4.7% of patients enrolled on a phase I dose-escalation study of the CHK1/2 inhibitor AZD7762 (AstraZeneca) in combination with gemcitabine, 49 praxasertib has not been associated with this feared side effect, even at the maximal tolerated dose. 50 As we have learned from difficulties combining high-potency PARPi with chemotherapy due to toxic myelosuppression, the sequential administration of chemotherapy followed by maintenance PARPi has led to clinical approvals, and this may be the required approach for novel ATRi–WEE1i–CHK1i.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%